(untitled) (Paliativní medicína, 2023)
We present a case study of a young patient with therapeutically refractory diffuse large B-cell lymphoma, emphasizing the collaboration between hemato-oncology and palliative care physicians at the General University Hospital (VFN) in Prague. Using a specific example, we illustrate the role of the hemato-oncologist, who discusses the therapeutic plan and potential treatment complications with the patient, while also assessing the family background of the patient. Additionally, we highlight the contribution of the palliative care team in managing a patient in a complex social situation and non-compliance with therapy. The contribution of the palliative care team for the patient in a complex social situation and non-compliant with therapy was effective. This intervention not only built trust between the patient, the palliative team, and the hemato-oncologists but also secondarily contributed to overall improved communication, higher treatment adherence, effective social support, and care aligned with the values and preferences of the patient.